Experimental Investigation of Pressure Drop in one Phase Flow, Particle-Liquid Two-Phase Flow, and Porous Media consisting of the Same Particle Size - Aybar, Hikmet S.; Sharifpur, M.; Vaziri, R. (Trans Tech Publications Ltd, 2009)
Many researches have performed some studies about pressure gradient in the one phase flow, particle-liquid two-phase flow and porous media. However, there is no any report about interaction among them. In this study, this interaction idea is developed by using the same particle size for particle-liquid two-phase flow and porous media. For the experimental study, an apparatus is designed, and at the first step one phase water pressure gradient is investigated, next in the further steps, little by little spherical particles are added to the cycle till accumulation of the particles did not allow any movement to the particles (i.e. porous media occur), and after that well pack porous media is investigated. The results confirm the relation between pressure gradient over mass flow rate in the one phase flow, particle-liquid two-phase flow and porous media obeys as a parabolic curve.
4th International Conference on Diffusion in Solids and Liquids -- JUL 09-11, 2008 -- Barcelona, SPAIN
Keywords: Porous media; particle-liquid two-phase flow; pressure drop